Attraction Methods in Paper vs. Online Diletant Magazine - Maria M. Sergeeva; Kapitalina V. Sinegubova (Виртуальная коммуникация и социальные сети, 2024)
The article introduces attraction marketing methods employed by Russian monthly popular science magazine Diletant. The authors compared the printed version and the website. The paper magazine attracts the reader mainly by the topic name printed on its cover as a unique creolized text. The further semantics of the front media text includes various aspects of the main topic. Color highlights both topical issue and regular features. The comparative analysis with the online version revealed some significant differences. The website has a muted color scheme and minimal animation; it contains neither video nor audio materials. Like in the printed version, the function of attraction belongs mainly to illustrations and subtitles. Online Diletant is interactive in navigation, tests, and surveys, which are, however, the only form of interactivity: the site does not provide comments, forums, “likes”, etc. Such limited use of attention-seeking tools makes the digital version of Diletant uncompetitive and inferior to its paper issue.